The Effect of Social Media and Service Quality on Blood Donor Participation at UDD PMI Klaten Regency - Viora Valenzania; Abdul Rahman; Yuhastina Yuhastina (Jurnal Mantik, 2022)
This study aims to determine the effect of social media and service quality on blood donation participation in the Indonesian Red Cross Blood Donor Unit, Klaten Regency. The research method used in this research is a quantitative approach. The participants in this study were blood donors at the Indonesian Red Cross Blood Donor Unit, Klaten Regency. The sample in this study consisted 95 respondents who were selected using a random sampling technique. Data collection techniques with documentation and questionnaires. The product moment correlatioin test and the multiple linier regression test were used to analyze the data. Based on the Multiple Linear Regression Test, the equation model Y = 1.68 + 0.13 X1 + 0.21 X2 is obtained. Meanwhile, based on the correlation test, the following results were obtained: (1) there is a significant effect of social media on blood donor participation (rcount 0.522 > 0.199 rtable; p > 0.1); (2) there is a significant effect of service quality on blood donor participation (rcount 0.603 > 0.199 rtable; p > 0.1); (3) there is a significant effect of social media and service quality on blood donor participation (Rxy 0.626 > 0.199 Rtable; Sig = 0.000 < 0.1).  This study concludes that there is a positive and significant effect of social media (X1) and service quality (X2) on blood donor participation (Y) in the Indonesian Red Cross Blood Donor Unit, Klaten Regency.